TINJAUAN YURIDIS SANKSI BAGI PELAKU PENYIMPAN PSIKOTROPIKA DALAM PENCALONAN KEPALA DAERAH: Juridical Review of Sanctions for The Perpetrators of Storing Psychotropic Substances in The Nomination of Regional Heads - Victory, Haura Ayu; Wiratno (Faculty of Law, Universitas Trisakti, 2024)
The findings of the literature research provide a description of the procedure for nominating regional leaders in line with Law No. 10/2016 on Regional Head Elections. This thesis also explains how, in line with Constitutional Court Decision No. 2/PUU-XX/2022, sanctions are applied to regional head nominees who violate the law. This thesis combines qualitative research with normative legal research methodologies to apply a statutory approach. The nature of this research is descriptive. The combination of primary, secondary, and tertiary legal documents with secondary data is the data source utilized. The methodology for data analysis employed is the descriptive approach, and the strategy for gathering data is the literature study. A qualitative approach is employed in the methodology of data analysis. The following conclusions are drawn from the study's findings: First, the nomination of regional heads based on Constitutional Court Decision No. 2/PUU-XX/2022 no longer prohibits those who have committed disgraceful acts, such as gambling, intoxication, drug use and trafficking, adultery, and other acts against decency, as stated in Law 10/2016's Article 7 paragraph (2) letter i. Once a person has completed their term and made an honest and public announcement, they are eligible to compete for regional head elections despite having done reprehensible conduct. Secondly, clauses pertaining to the nomination of regional heads are included in the sixty-seven provisions changed in Law No. 10/2016 on Regional Head Elections. Most of these changes were, at the very least, brought forth in reaction to multiple decisions made by the Constitutional Court that struck down specific sections of Laws 1/2015 and 8/2015. Law 10/2016 also implements many additional modifications that are considered necessary to facilitate the holding of regional elections in November 2020 and 2024.